2021
DOI: 10.3390/ijerph18178900
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Indoor and Outdoor Particulate Matter 2.5 in Selected Residential Areas near a Ferromanganese Smelter

Abstract: Particulate matter (PM) of different sizes and elemental composition is a leading contributor to indoor and outdoor air pollution in residential areas. We sought to investigate similarities between indoor and outdoor PM2.5 in three residential areas near a ferromanganese smelter in Meyerton to apportion the emission source(s). Indoor and outdoor PM2.5 samples were collected concurrently, using GilAir300 plus samplers, at a flow rate of 2.75 L/min. PM2.5 was collected on polycarbonate membrane filters housed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…6-8 Furthermore, exposure per unit mass of PM 2.5 released from indoor sources is between two to three orders of magnitude larger than in outdoor environments. 9,10 Studies 11,12 have found that the concentration of indoor PM 2.5 tends to be higher than the outdoor in many cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-8 Furthermore, exposure per unit mass of PM 2.5 released from indoor sources is between two to three orders of magnitude larger than in outdoor environments. 9,10 Studies 11,12 have found that the concentration of indoor PM 2.5 tends to be higher than the outdoor in many cases.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 8 Furthermore, exposure per unit mass of PM 2.5 released from indoor sources is between two to three orders of magnitude larger than in outdoor environments. 9 , 10 Studies 11 , 12 have found that the concentration of indoor PM 2.5 tends to be higher than the outdoor in many cases. This is concerning given that in modern society people spend 90% of their time in confined indoor environments such as offices, classrooms, homes, and laboratories.…”
Section: Introductionmentioning
confidence: 99%